Association between dietary pattern, atherogenic index of plasma, and cardiovascular disease risk factors amongst adults: A cross-sectional cohort-based study - Mehrab Sayadi; Pouria Azami; Mohammad Javad Zibaeenezhad; Nasrin Motazedian; Fatemeh Khademian; Mohaddeseh Hasanzadeh; Fatemeh Zibaeenejad; Seyyed Saeed Mohammadi; Houri Mousavinezhad; Zahra Daneshvar; Nader Parsa; Iman Razeghian-Jahromi (PLoS ONE, 2026)
Background and aims This study aims to examine the association between dietary patterns, the atherogenic index of plasma (AIP), and cardiovascular risk factors in adults aged 40–70 years in southern Iran. Methods and results Participants’ dietary patterns were assessed using a Food Frequency Questionnaire with 35 food groups. Dietary patterns were categorized using Principal Component Analysis into three groups: Vegan, Western, and Carbohydrate-based. AIP was calculated as the log (triglycerides/HDL-C), and cardiovascular risk was assessed using a standard prediction model. Participants were classified based on their adherence to dietary patterns, and their cardiovascular risk was assessed. A total of 1,675 participants were included (mean age 53.4 ± 8.3 years; 43.5% men). The high AIP group had higher ASCVD risk scores (7.0 ± 7.7) compared to the low (3.9 ± 5.5) and intermediate-risk groups (3.9 ± 5.1). High adherence to the vegan diet was associated with lower AIP (0.41 ± 0.22) compared to low adherence (0.46 ± 0.23), with an adjusted β of −0.047 (95% CI, −0.072 to −0.021; P < 0.001). In contrast, neither Western (high: 0.45 ± 0.23 vs. low: 0.44 ± 0.23) nor carbohydrate-rich diets (high: 0.45 ± 0.23 vs. low: 0.44 ± 0.22) showed significant associations with AIP. Conclusion The findings suggest that high adherence to a vegan diet is beneficial for cardiovascular health, as evidenced by lower AIP, a marker of atherosclerosis risk. It highlights the potential role of dietary interventions in reducing cardiovascular risk, with a focus on plant-based diets for improving lipid profiles and heart health.